Colloquial French CD-ROM a multimedia language course (New York, N.Y. Routledge, 1998)
Provides 19 interactive lessons in French covering a range of everyday travel, business and leisure situations. Speech recognition and record/playback function help the user in improve pronunciation.
Title from disc label.
System requirements: 486 Windows-Compatible personal computer; 2 MB available hard disk space; double-speed CD-ROM drive; Microsoft extensions (MSCDEX) 2.2 or higher; Microsoft Windows 3.1 or higher; Audio card; Speakers and microphone; VGA or SVGA (256 colors) with graphic card; Mouse.
Keywords: French language -- Spoken French -- Study and teaching -- Software; French language -- Study and teaching -- Software; French language -- Computer-assisted instruction for English speakers -- Software